Early postoperative complications have long-term impact on quality of life after restorative proctocolectomy. Issue 27 (July 2016) - McCombie, Andrew; Lee, Yun; Vanamala, Rutvik; Gearry, Richard; Frizelle, Frank; McKay, Emma; Williman, Jonathan; Eglinton, Tim
Abstract: Introduction: Early postoperative complications graded according to the Clavien–Dindo classification system have not previously been correlated with long-term quality of life outcomes in patients who have had restorative proctocolectomy with ileal pouch-anal anastomosis. This study aimed to assess the severity of early postoperative complications and compared these in terms of the long-term quality of life after restorative proctocolectomy in a population-based cohort of patients (operated on from 1984 to 2013). It was hypothesized that those who experienced grade 3 or 4 Clavien–Dindo complications would have worse quality of life at follow-up. Methods: This population-based study used a combination of a retrospective note review and a cross-sectional questionnaire. All patients with a restorative proctocolectomy performed in 1984–2013 in the Canterbury region were recruited using multiple sources. Early (⩽30 days) and late (>30 days) complication rates were obtained via patient records. Early postoperative complications were graded according to the Clavien–Dindo classification. Quality of life was measured using the inflammatory bowel disease questionnaire. Results: One hundred and thirty-six people were identified with a median follow-up of 12 years. Data were available for 121 patients for early complications and 112 for late complications. Eighty-one eligible participants had their quality of life assessed (86% response rate). Early complications occurred in 26% and 76% had late complications. Those who had Clavien–Dindo grade 3 or 4 early complications had lower quality of life scores ( P = 0.001) as did females ( P = 0.004) and those with a stricture ( P = 0.031). Conclusion: This population-based study with long-term follow-up demonstrates that Clavien–Dindo grade 3 and 4 postoperative complications are important in determining quality of life in the long term. The reduction in these complications should be a focus of patient management, as it should improve long-term quality of life.